The relationship between childhood trauma and depressive symptom among Zhuang adolescents: Mediating and moderating effects of cognitive emotion regulation strategies - Yin, Wenwen; Pan, Yuli; Zhou, Linhua; Wei, Qiaoyue; Zhang, Shengjie; Hu, Hong; Lin, Qinghong; Pan, Shuibo; Dai, Chenyangzi; Wu, Junduan (Frontiers in Psychiatry, 2022)
Background: Not all adolescents who have endured childhood trauma will develop depression, nor will they all experience the same level of depression. According to previous research, cognitive emotion regulation strategies may explain a portion of the variance. Observe the connection between childhood trauma and depression and investigate whether cognitive emotion regulation strategies mediate or moderate this association. Methods: In October 2019, a cross-sectional study measuring childhood trauma, cognitive emotion regulation strategies, and depression among Zhuang adolescents was done in one senior high school and two junior highs in Chongzuo, Guangxi, China, using a self-report questionnaire. To examine the hypothesis of mediating and moderating effects, SPSS PROCESS was utilized. Results: In a sample of 1132 students, 49.4% were male, 50.6% were female, and the average age was 14.66 years (SD =1.441). In this study, there was a positive association between childhood trauma and depression, whereas there were positive correlations between expressive suppression and childhood trauma and depression (r=0.380, 0.246, and 0.089, respectively, p<0.01). And emotional abuse, a type of childhood trauma, was significantly linked with depression, whereas expressive suppression was positively connected with depression and emotional abuse (r=0.466, 0.246, and 0.148, respectively, p<0.01). The 5000-sample bootstrap procedure revealed that the indirect relationship between the independent variable (childhood trauma or emotional abuse) and the dependent variable (depression) was statistically significant (β =0.0154 95%CI:0.0019,0.0165, β =0.0442 95%CI: 0.0008,0.0117). The statistical significance of the interaction effect enhanced the R-square value of the moderating effect when the independent variable was the total childhood trauma score (ΔR2 = 0.0044, 0.0089). Conclusions: Our findings corroborated the conclusion of prior research that cognitive emotion regulation strategies mediate and moderate the depressive process. Although we demonstrate that cognitive emotion regulation strategies play a mediating and moderating role in the relationships between childhood trauma and depression, the mediating effects on the relationships between the other types of childhood traumas, including physical abuse and neglect, sexual abuse, emotional neglect, and depression, did not emerge.